An Archeology of Global Images' Languages: The Picturesque Case (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2021)
The book by Timothy Brook, Vermeer’s Hat, The Seventeenth Century and the Dawn of the Global World (2009) shows how in that age, a lot of handcrafts – such as hats and porcelain – entered Europe through the massive trading activities of Dutch East India Company. To illustrate this, he conducts an in–depth analysis of Vermeer’s canvases. Brook’s inquiry therefore shifts the dawn of the globalized world – a marker of our contemporary age – to a time when some countries brought to life a world where a network of connections and exchange was arising in a way never seen before. The Age of Discovery was over, and the Age of Imperialism was still to come. Meanwhile, when trading and cultural exchange began, the ‘translation’ of languages from one world to another was required for understanding and eventually integration. First the Dutch and then the English adopted an image language capable of describing both new worlds and home environments in the same way, thus making new situations and different landscapes easy to access and understand for people viewing them in the homeland. There was therefore a sort of ‘transmigration’, an attempt to adapt visual codes the Picturesque to overseas environments and landscapes. In other words, well–established pictorial codes were employed as a ‘lens’ to look at a unique, faraway place. For a long time, up to the invention of photography, the Picturesque was the global language used to make even very faraway, exotic places familiar, and in doing so, re–inventing overseas landscapes through the European cultural matrix. This paper uses several iconographic cases to illustrate how the Picturesque became a global code, a kind of ‘common language’ representing different, faraway cultures through a Western pictorial language.
Keywords: globalization; Picturesque; visual culture